1993
DOI: 10.1902/jop.1993.64.2.103
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Polylactic Acid Granules and Decalcified Freeze‐Dried Bone Allograft in Human Periodontal Osseous Defects

Abstract: The purpose of this study was to compare the effectiveness of polylactic acid (PLA) granules as an alloplastic grafting material to that of decalcified freeze-dried bone allograft (DFDBA) and a flap procedure for debridement without graft (FPD) when treating periodontal intrabony defects. Ten patients presenting with advanced adult periodontitis, including at least 3 similar periodontal osseous defects (2- and 3-walled), comprised the study group. After completion of a hygienic phase of treatment, measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…[2526] Hence, probably, allograft material could have promoted the healing in the present case. However, only objective of using bone graft material in this case was to produce an apical barrier.…”
Section: Discussionmentioning
confidence: 91%
“…[2526] Hence, probably, allograft material could have promoted the healing in the present case. However, only objective of using bone graft material in this case was to produce an apical barrier.…”
Section: Discussionmentioning
confidence: 91%
“…Two articles (Meadows et al 1993, Shahamiri et al 1992), although they were included in the systematic review, could not be included in the meta‐analysis because it was not possible to estimate SE of the mean effect for outcome variables. Figure 1 gives a flow chart of studies assessed and excluded at various stages of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been carried out to evaluate the efficacy of bone allograft materials in the regeneration of periodontal osseous defects. In general, these studies have shown significant radiographic bone fill and significant improvement in probing depth measurements and clinical attachment levels following treatment with demineralized freeze‐dried bone allograft (DFDBA) compared with other treatment modalities (3). These studies have attributed the osteoinductive and osteoconductive potentials of DFDBA to bone‐inductive components such as bone morphogenetic proteins (4).…”
mentioning
confidence: 99%